Best practice guideline for management of gastrointestinal (GI) infections, including traveller`s diarrhea, in elite road cyclists - Heron, N.; Gonzalez, J.; Moran, J.; Prieto, A.; Elliott, J. (Journal of Science and Cycling, 2021)
This best practice guideline and infographic describe the prevention and management of gastrointestional (GI) infections, with a particular focus on Traveller`s diarrhea (TD). This best practice guide has been developed for use in elite road cycling.